Sérgio Abreu e seu tempo - Amorim, Humberto; Dias, Ricardo; de Almeida Ribeiro, Felipe; Poletto, Fabio (Revista Vórtex, 2023)
“Sérgio Abreu e seu tempo”, volume 1 da série de Ebooks da Revista Vórtex. Humberto Amorim, Ricardo Dias, Felipe de Almeida Ribeiro, Fabio Guilherme Poletto (organizadores)